Indução experimental de acidose ruminal e laminite em bezerros mestiços pela administração intrarruminal de oligofrutose - Noronha Filho, Antônio Dionísio Feitosa (2017)
Among diseases that can affect cattle in intensive production systems are rumen acidosis laminitis. It was produced initially a literature review about experimental induction of rumen acidosis and after this, was evaluated rumen acidosis and initial phase of laminitis in calves, both induced by intrarruminal administration of oligofructose. In the different protocols, in both acute and subacute forms of acidosis, are usually evaluated fermentative and clinical aspects. In the study was used six crossbred male calves (Bos taurus X Bos indicus) aging one year and weighting 175 ± 22,6 kg. Initially were used three animals in a pilot group (GP), receiving oligofructose in the dose of 13g/kg and after this, three animals were used as experimental group (GE) receiving oligofructose in the dose of 17 g/kg. Were evaluated parameters from clinical exam, hematocrite, plasmatic protein, blood gas analysis and histology of hoof samples. Oligofructose overload induced rumen acidosis in both groups. It was also observed metabolic acidosis with reduction of blood pH, PCO2, bicarbonate and base excess. Was observed neither elevation in hoof sensibility nor lameness. Despite this, many animals presented apathy and slower gait, possibly due to metabolic acidosis. In histologic evaluation, were observed circulatory changes and inflammatory infiltrate in dermis, irregularities in basement membrane and morphologic changes in basal epidermis. Protocol for laminitis induction with intrarruminal administration of oligofructose in crossbred calves was well succeeded. In the initial phase, laminitis was characterized by clinical signs of the primary disease, in this case rumen acidosis, and histologic lesions indicative of acute inflammation and compromise of basement membrane and basal epidermis.